2011
DOI: 10.1074/jbc.m111.287201
|View full text |Cite
|
Sign up to set email alerts
|

PEX5 Protein Binds Monomeric Catalase Blocking Its Tetramerization and Releases It upon Binding the N-terminal Domain of PEX14

Abstract: Background: PEX5 binds newly synthesized peroxisomal proteins in the cytosol and releases them in the organelle matrix. Results: PEX5 binds monomeric catalase and releases it in the presence of PEX14. Conclusion: PEX14 participates in the cargo release step. Significance: Knowing how PEX5 interacts with cargo proteins and which factors disrupt this interaction are crucial for understanding this protein sorting pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
104
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(113 citation statements)
references
References 89 publications
7
104
0
Order By: Relevance
“…Interestingly, a stable subcomplex consisting of Pex5 and Pex14 with a 1:5 stoichiometry could be isolated from rat liver peroxisomes (6). Finally, Pex14 binding to the downstream-located WXXX(F/Y) motifs six and seven triggers cargo release (10). Pex13 might also play a critical role in pore assembly or disassembly because it was shown that WXXX(F/Y) motifs 2-4 of Pex5 are able to interact with this peroxin (13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, a stable subcomplex consisting of Pex5 and Pex14 with a 1:5 stoichiometry could be isolated from rat liver peroxisomes (6). Finally, Pex14 binding to the downstream-located WXXX(F/Y) motifs six and seven triggers cargo release (10). Pex13 might also play a critical role in pore assembly or disassembly because it was shown that WXXX(F/Y) motifs 2-4 of Pex5 are able to interact with this peroxin (13).…”
Section: Discussionmentioning
confidence: 99%
“…For the model organism Saccharomyces cerevisiae, it was shown that Pex14 together with Pex5 constitutes a large dynamic channel at the peroxisomal membrane, which is supposed to act as a protein conducting pore (9). Recent data suggest that the Pex14-Pex5 interaction also plays a critical role for release of the cargo protein into the lumen of the peroxisome (10).…”
Section: In Human Cells This Interaction Is Mediated By Seven Consermentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has been shown that the C-terminal half of PEX5 has a crucial role in the interaction with the PTS1 (13,14), it is becoming increasingly apparent that the N-terminal half of PEX5 also contributes to the interaction with cargo proteins (16 -20). Interestingly, recent data suggest that PEX5 may also act as a chaperone/holdase at least for some peroxisomal matrix proteins (16).…”
mentioning
confidence: 99%
“…However, the import machinery prefers monomeric proteins (Freitas et al, 2015), and PEX5 binding to catalase (Freitas et al, 2011), acyl-CoA oxidase1, and urate oxidase (Freitas et al, 2015) prevents oligomerization of these cargo proteins.…”
Section: Matrix Protein Import: Cycling Receptorsmentioning
confidence: 99%